Immigrant versus Native Businesswomen : Proclivity and Performance - Amelie F. Constant (Institute for the Study of Labor (IZA), 2004)
Career positions in German economic life are still male-dominated, and the driving forces behind success are not yet well understood. This paper contributes to a better understanding by classifying success stories in self-employment and business careers, and by investigating differences between native women (both from West and East Germany) and migrants using a rich data set from the German Socio-economic Panel. Results on self-employment proclivity are very sensitive to the alternative choice. Women choose self-employment over a business career in the salaried sector when they are older, less educated, have under-age children, and parents who are self-employed themselves. When women are younger and more educated but have children, they choose self-employment as a way to circumvent unemployment. Women who are more educated and do not have under-age children are more likely to be businesswomen in the salaried sector, suggesting a clear choice for a secure job. East German women are less likely to choose self-employment or a business career than West German women. Overall, compared to other types of employment, selfemployment offers women the desirable and valuable element of time and space flexibility. Businesswomen in paid-employment earn the highest wages and this is long-lasting. Compared to women in lower dependent employment, those in self-employment earn more. Thus, self-employment offers women a path to economic success. Invariably, East German women earn less than West German women.
Keywords: J15; J31; J61; J16; J24; M13; J23; 330; entrepreneurship; self-employment; occupational choice; economics of minorities; economics of gender; immigrants; Frauenarbeitslosigkeit; Berufswahl; Unternehmer; Selbstständige; Weibliche Führungskräfte; Migranten; Schätzung; Erwerbsverlauf; Deutschland